2015
DOI: 10.1080/03075079.2015.1049143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an academic dismissal policy on dropout, graduation rates and student satisfaction. Evidence from the Netherlands

Abstract: This paper examines the effect of the introduction of an academic dismissal (AD) policy (i.e. an intervention which can lead to compulsory student withdrawal) on student dropout, student graduation rates and satisfaction with the study program. Using a Difference-in-Differences type of estimator, we compare programs that introduced an AD policy with a control group of programs which did not employ an AD policy. The robustness of the results is tested by a propensity score matching. The outcomes suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
1
19
0
3
Order By: Relevance
“…Research on the use of academic probation for low-performing students shows that probation encourages some students to drop out, while improving grades for those students who decide to stay in the course programme (Lindo, Sanders, and Oreopoulos 2010). On the other hand, previous research on Dutch assessment policies showed higher first-year dropout rates (Arnold 2015;Sneyers and De Witte 2017), as well as lower grades (De Koning et al 2014) under academic dismissal policies. Results on academic progress were mixed, showing either no increase in progress (Stegers-Jager et al 2011;Eijsvogels et al 2015), or even a slight decrease in obtained credits (De Koning et al 2014) after the introduction of an academic dismissal policy.…”
Section: Height Of the Stakesmentioning
confidence: 98%
“…Research on the use of academic probation for low-performing students shows that probation encourages some students to drop out, while improving grades for those students who decide to stay in the course programme (Lindo, Sanders, and Oreopoulos 2010). On the other hand, previous research on Dutch assessment policies showed higher first-year dropout rates (Arnold 2015;Sneyers and De Witte 2017), as well as lower grades (De Koning et al 2014) under academic dismissal policies. Results on academic progress were mixed, showing either no increase in progress (Stegers-Jager et al 2011;Eijsvogels et al 2015), or even a slight decrease in obtained credits (De Koning et al 2014) after the introduction of an academic dismissal policy.…”
Section: Height Of the Stakesmentioning
confidence: 98%
“…Furthermore, policy interventions shown to be effective in some schools have proved unsuccessful in other disciplines, and their effectiveness depends on characteristics of the student population . Additionally, although data on the possible side‐effects of these policy interventions are lacking, there is increasing fear that such measures imply a cost to student well‐being …”
Section: Introductionmentioning
confidence: 99%
“…There are some uncommon exceptions which also make students eligible for university (e.g. colloquium doctum), which are described in detail in Sneyers and De Witte (2017). Students who enter university start with a bachelor's program (typically 3 years), after which they either enroll in a 1 (or 2) year(s) master's program or enter the job market.…”
Section: The Dutch Higher Education Systemmentioning
confidence: 99%
“…guiding a student to a program in which one is more likely to succeed) (Onderwijsraad 2008;de Koning et al 2014). In the Netherlands, AD policies have been implemented ever since the late 1990s, with results suggesting that programs that installed such policies experienced higher first-year dropout and higher graduation rates (for the remaining students), when compared to similar programs without AD (Sneyers and De Witte 2017). By 2009, roughly half of the university bachelor programs had an AD policy in place (Dutch Inspectorate of Education 2010).…”
Section: Introductionmentioning
confidence: 99%